Antioxidant activity and in vitro cytotoxicity study of the phenolic compounds from piper sarmentosum. - Ibrahim, Maizatul Akma; Ghazali, Nor Farahiyah; Mustafa, Farah Farisha; Abdul, Nurul Huda; Tengku Muhammad2, Tengku Sifzizul (2019)
Cancer is by far one of the most worrying health issues that continues to be the major killing diseases worldwide, accounting for more than 6 million deaths. In the confrontation of advances in modern medicine such as surgery, chemotherapy, radiotherapy and hormone therapy, cancer disease persists a worldwide problem. Thus the search for new potential anticancer agents avertable to human malignancies is highly demanded. Since the past few years, the search for new alternatives has been concentrated in finding medicinal herbs from local natural resources. Approximately, 60% of currently applied cancer drugs are derived from natural sources, due to its fewer side effects. Piper sarmentosum Roxb. which is locally known as ‘kaduk’, is one of natural medicinal plant that had been used traditionally to treat headache, arthritis, menstrual pain, cough and eczema. It is proven to have various biological properties such as anti-inflammatory, antioxidant, antimalarial, antiplasmodial, anti-diabetic, antifungal and anticarcinogenic. The aims of this study were to identify the phenolic compounds of P. sarmentosum methanolic extracts by measuring total phenolic content, and HPLC analysis. The antioxidant activity was evaluated by DPPH scavenging assay. MTS assay was also conducted to study the effect of the extracts on human breast cancer cells, MCF-7. The HPLC analysis showed the presence of quercetin, naringin, gallic acid and tannic acid in P. sarmentosum. P. sarmentosum exhibited antioxidant property at 96.98 ± 2.29 μg/mL by DPPH scavenging activity with its high phenolic content at 89.22 mg GAE/ g dry extract. The cytotoxicity screening of P. sarmentosum extract using MTS assay provided IC50 of 24.63 ± 0.23 μg/mL on MCF-7 cells. In conclusion, the phenolic compounds obtained from P. sarmentosum possess potent antioxidant and anticancer activity against the tested breast cancer cells. Further study might focus on the compounds action mechanisms toward the tumour cells.